ریاست مدینہ میں قیام امن کے لیےمعاہداتِ نبوی (ایک اختصاصی مطالعہ): Prophetic Treaties for Peace in the State of Madina (A Specific Study) - Ajmal Ali; Dr. Zahoor Ali Alazhari (MEI, 2023)
The Holy Prophetﷺmade several treaties to createﷺPeaceful state and good neighborly relations with neighboring tribes and Counteries of the Islamic State. He integrated the Jews and the Muslims intoﷺcollective unity through Medina Peace Treaty. By virtue of this agreement, they acknowledged him the ruler of their city, and agreed to abide by his decisions in all disputes. The udaybiya Treaty was another peace treaty of its own kind. The Prophetﷺaccomplished this peace mission and achieved the results which no war could have gained. There is no better proof than this treaty of the repudiation of war, as an instrument of policy, and of his genuine love of peace.These treaties are effective means of ensuring peace and security and to strengthen the provision of human rights. Such was the strategy the Messenger of peaceﷺemployed to ensure the protection of people from bloodshed, massacres, oppression, violations of human rights, injustice, corruption, immorality and socio-economic evils. Breaking the vicious cycle of killing and vengeance, forging the Emigrants and the Helpers as well as the Jews together through the written constitution and concluding treaties with scores of tribes of the Jews and the Christians, he established lasting and ever-spreading peace in the world.